2012
DOI: 10.12968/bjom.2012.20.8.558
|View full text |Cite
|
Sign up to set email alerts
|

Birthing outcomes from an Australian HypnoBirthing programme

Abstract: Background and aim: HypnoBirthing, which is steadily increasing in popularity both in Australia and overseas, is a set programme consisting of 10–12 hours of instruction for couples approaching the later stages of pregnancy and birth. A survey was carried out to investigate how Australian participants attending the HypnoBirthing programme between 2007 and 2010 compared to other studies where hypnosis was used for childbirth. Results: The average length for both stages of labour was shorter in the HypnoBirthing… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
4
0
2

Year Published

2016
2016
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 24 publications
1
4
0
2
Order By: Relevance
“…The difference between the groups in the method of delivery is important in terms of showing that the vaginal delivery rate was high in the group that received hypnobirthing training and that this training was effective in reducing the rates of emergency and elective cesarean section. Similar to the cesarean section rate (18.4%) of the women who received hypnobirthing training in our study, the rate of cesarean delivery in women who received hypnobirthing training was 17.1% in the study of Swencionis et al (2012) and 22% in the study of Phillips -Moore (2012). A significant difference was reported between them.…”
Section: Discussionsupporting
confidence: 88%
See 2 more Smart Citations
“…The difference between the groups in the method of delivery is important in terms of showing that the vaginal delivery rate was high in the group that received hypnobirthing training and that this training was effective in reducing the rates of emergency and elective cesarean section. Similar to the cesarean section rate (18.4%) of the women who received hypnobirthing training in our study, the rate of cesarean delivery in women who received hypnobirthing training was 17.1% in the study of Swencionis et al (2012) and 22% in the study of Phillips -Moore (2012). A significant difference was reported between them.…”
Section: Discussionsupporting
confidence: 88%
“…This finding showed that hypnobirthing training was effective in shortening the delivery time. In a study conducted with an Australian hypnobirthing program, the women participating in the program gave birth in a shorter time and there was a significant difference between the groups (Phillips -Moore, 2012).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Teknik relaksasi Hypnobirthing adalah program untuk menanamkan sugesti kea lam bawah sadar, menerima kehamilan dengan baik, mereprogramming sugesti negative bahwa ''melahirkan itu sakit''dengan sebuah afirmasi dan sugesti positif tentang sebuah persalinan yang indah, nyaman, lancer dan alami. Menyadari kekuatan terbesar pada tubuh serta menyerahkan semuanya tentang proses persalinan kepada tubuh dan bayi sehingga harapannya tubuh, bayi dan ibu dapat bekerjasama dengan baik untuk menjalani sebuah persalinan yang aman dan nyaman serta bebas trauma (Phillips-Moore, 2012).…”
Section: Pembahasanunclassified
“…Hypnotherapy for labour and birth is based upon the premise that a woman's fear and stress of labour and birth leads to muscle tension and ultimately increased pain which incites further fear and stress, continuing the cycle (Phillips-Moore, 2012). Using Hypnotherapy, a woman can be taught to work with her body's natural processes in order to reduce feelings of fear, helplessness, tension and pain.…”
Section: Introductionmentioning
confidence: 99%